¿Incluyen las Universidades Argentinas la Sostenibilidad en sus Actividades de Extensión? - Arias-Valle, María Belén; Marimon, Frederic (Luna Azul, 2025)
This study examines the integration of sustainability into university extension activities within Argentine Higher Education Institutions (HEIs). It investigates how both public and private institutions have incorporated sustainable development initiatives into their extension programs, particularly in light of the limitations imposed by Law 27.621, which excludes extension as a pillar of environmental education. Using a quantitative approach, a descriptive and correlational analysis was conducted based on data collected from the websites of 132 HEIs. The findings reveal that only 21% of institutions have embedded sustainability into their extension activities, with public HEIs exhibiting a stronger commitment than their private counterparts. Key success factors include the inclusion of sustainability in institutional missions and the establishment of strategic alliances. However, policy implementation remains fragmented, hindering systemic impact. Despite progress, persistent challenges include resource constraints and the need for more cohesive national policies to ensure uniform adoption of sustainable practices across all HEIs. This study offers recommendations to enhance the role of university extension in advancing sustainable development, emphasizing the importance of dedicated institutional leadership and strategic planning aligned with the Sustainable Development Goals (SDGs).